Epilepsy in children and adolescents: disease concepts, practical knowledge, and coping - Pauschek, Josefine; Syrbe, Steffen (Epilepsy & behavior, 2016)
Problem - Children suffering from epilepsy face severe difficulties in daily life. However, data about the self-assessment of children are scarce. - Methods - From October 2013 to February 2014, patients aged 6-18years suffering from epilepsy were consecutively invited (i) to take part in a structured interview and (ii) to draw a picture about their self-assessment of epilepsy. - Results - Eighty-four children and their parents agreed to participate: (i) 63/84 (75%) of the children named their disease correctly; contagiousness was assumed by 8/84 (10%); 81/84 (96%) knew whether they have to take medication; 36/69 (52%) of the children taking long-term medication reported the name(s) of their medication; 8/69 (12%) believed that their medication will cure their disease; 45/84 (54%) named specific precautions to prevent harm from seizures; 6/84 (7%) believed that nonadherence to safety precautions would cause new seizures; and 23/84 (27%) believed that they are worse off than healthy children. (ii) 67/84 (80%) drew a picture titled “This is how I feel when I have a seizure”. Specific symptoms [17/67 (25%)] and the interaction between child and environment [12/67 (18%)] were the most common subjects. - Conclusion - Most children with epilepsy had rather good knowledge about medication; half of the children knew specific safety precautions. The children were often able to describe their seizures well. Pictures drawn by patients can give an insight into their experiences. Teaching programs should, among others, address the fear of contagiousness of epilepsy in some children and the fact that children with epilepsy might feel disadvantaged.
Gesehen am 16.08.2019